(untitled) (Balneo and PRM Research Journal, 2021)
Introduction. Endocrino-metabolic rehabilitation represent one of the most complex sector in clinical medicine, regarding functional rehabilitation. Sex hormones deficiency plays an important role in the etiology of osteoporosis in men. At the same time, with age, the trophic role of androgens on muscle decreases and determines an increased frequency of falls. The objective of our study is to determine the association between sexsteroids deficiency, reduction of bone mineral density (BMD) and falling risk in men. Methods. Our retrospective cross-sectional study included 146 men aged between 65–85 years with low BMD (study group) and 121 men with normal BMD (control group). The measurement of Total testosterone (Tt), free testosterone (Tf) and estradiol (E2) serum levels was performed using the immunoassay or the immunoenzymatic methods. Femoral neck and lumbar spine BMD was determined using Dual-energy X-ray absorptiometry (DEXA). The risk of falls was assessed by Tandem Standing, Up & Go, Chair – Rising and walking speed tests. Results. We found a significantly association between Tf and E2 deficiency and low BMD (p=0.007). Also, in men with reduced BMD (study group) we observed significant lower levels of Tf (p<0.001) and E2 (p=0.003) compared to control group. E2 deficiency was associated significantly with low BMD and increased fall risk (p=0.001). At the same time the results highlighted significant lower levels of Tf in patients with BMD reduction and increased risk of falls (p=0.002). Tt deficiency was not associated with BMD reduction (p=0.088) or increased risk of falling (p=0.277). Conclusions. This research revealed a significant association between male sexsteroids deficiency, low BMD and increase of falling risk, with implications in rehabilitation program. The risk of ostoporosis and for falling in man can be estimated by determining serum Tf and E2 levels.